2019
DOI: 10.24099/vet.arhiv.0700
|View full text |Cite
|
Sign up to set email alerts
|

Haematology in the early diagnosis of cattle diseases - a review

Abstract: Laboratory blood tests are not only an important element of the assessment of the general condition of animals, but they are also important for the early diagnosis of many diseases. In modern buiatrics laboratory tests are most frequently limited to the analysis of metabolic profiles, using selected biochemical tests. This reductionist approach results from economic reasons and ignores the possibility of using haematological tests, often limiting the possibility of a certain diagnosis. Haematology (Greek αιµα … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Findings from this study showed that the MP device, which monitors human blood erythrocyte parameters, 7 can be used in large animal veterinary practice to assist in diagnosing cattle diseases by examining variations in Hb concentrations and PCVs. 4 Comparison testing is mandatory when a portable human diagnostic device is used in other species for which the device has not been factory-calibrated. 11 The Hb and PCV values of cattle obtained with the MP device using blood collected with and without K 2 EDTA were positively correlated with the respective GS methods.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Findings from this study showed that the MP device, which monitors human blood erythrocyte parameters, 7 can be used in large animal veterinary practice to assist in diagnosing cattle diseases by examining variations in Hb concentrations and PCVs. 4 Comparison testing is mandatory when a portable human diagnostic device is used in other species for which the device has not been factory-calibrated. 11 The Hb and PCV values of cattle obtained with the MP device using blood collected with and without K 2 EDTA were positively correlated with the respective GS methods.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors affect cattle hematologic parameters, including hemoparasites, such as those which cause bovine sadness complex, toxic plant and metal intoxications, and infectious diseases, such as leptospirosis. 4 The pathogenesis of these diseases leads to hemolytic anemia that must be monitored by hematologic analyses, principally PCVs and Hb concentrations, especially in the cases with hemoparasites. 4 In addition to their importance for the early diagnosis of health conditions, these blood analyses are important when considering treatment options, such as measuring the difference between the initial and final PCV values (delta PCV), 5 which reinforces the need for accessible techniques in the field.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations